Society and Culture of the Indigenous People of Chittagong Hill Tracts of Bangladesh - Mekhala Chakma; Md. Kamrul Hasan (ISJN Journal, 2021)
The study of culture of the indigenous people of Chittagong Hill Tracts has a great significance. Chittagong Hill Tracts is situated in the south-eastern part of the present Bangladesh. Chittagong Hill Tracts is occupied by the different tribal groups who are the indigenous people of the region. Although works have been done on Chittagong Hill Tracts and its people, the different aspects of culture and the social structure, the mindset of the society has remained under-researched. The mentality of the society which has become the cultural norms and values through the ages remains an issue of great concern for this study. The purpose of the study was to explore and explain the society and culture of the indigenous people of Chittagong Hill Tracts by analyzing the material and immaterial aspects of culture like social institutions, etc. The methodology of the study is based on the information contained in work have been done on Chittagong Hill Tracts and the people, historical sources, gazetteers and other materials. In addition to this, folk lore, oral traditions, etc. have also been taken as important historical source. The results of the study have come out from the data are (a) in spite of differences the society and culture of the different indigenous groups have some similarities, (b) the principles of each group is unique, (c) the social structure and the mindset of the society shows discrimination between men and women, and (d) changes have been taken place in the society and culture over the period of time. Hopefully, the study will provide a deeper understanding about the culture and structure of the society of the indigenous people of Chittagong Hill Tracts which will help the future researchers, scholars, academicians and so on.